Effect of ion concentration on mechanosynthesis of carbonated chlorapatite nanopowders - Fahami, A.; Nasiri-Tabrizi, B.; Beall, G.W.; Pingguan-Murphy, Belinda (Materials Letters, 2015)
Carbonated chlorapatite nanopowders (n-CCAp) with different degrees of substitution were successfully synthesized by the one-step mechanochemical process. Results demonstrated that the formation of n-CCAp was influenced strongly by the carbonate content (x). From X-ray analysis, crystallite size, crystallinity degree, and unit cell volume of n-CCAp decreased significantly as carbonate content (x) increased from 0 to 2. Conversely, the lattice strain and the volume fraction of grain boundaries grew considerably. Microscopic analysis showed the average particle size of the synthesized powders was 15 +/- 10 nm. The influence of carbonate concentration on mechanosynthesis of pure n-CCAp utilizing a facile solid-state process has not been reported yet; it has potential application for biomedical engineering. (C) 2015 Elsevier B.V. All rights reserved.